The nature and origin of enclaves in four peraluminous granitoid intrusions from the Meguma Zone, Nova Scotia - Tate, Marcus (Atlantic Geology, 1994)
Four mid- to late Devonian peraluminous granitoid intrusions in the Meguma Zone of southwestern Nova Scotia contain abundant enclaves typical of orogenic granitoid bodies. The Barrington Passage and Shelbume plutons contain an assem blage of granoblastic metasedimentary homfelsic enclaves (49%) that have aluminosilicate porphyroblasts, and surmicaccous enclaves (51%) that consist of > 70% decussate biotitc with apatite and zircon inclusions. Metasedimentary enclaves pre dominate in the Port Mouton Pluton and the South Mountain Batholith (52%), but these intrusions also contain abundant microgranular and coarse-grained granitoid enclaves (25% and 23%, respectively) that have peraluminous mineral assem blages and tonalitic to leucomonzogranitic compositions. High concentrations of metasedimentary enclaves at the country rock contacts suggest that they probably formed as xenotiths stoped from the Meguma Group. No xenoliths reflect palaeosomes of basement gneiss from the protolith of the granitoid melts, but the surmicaccous enclaves may be restitc in the Port Mouton Pluton and the South Mountain Batholith; in the Barrington Passage tonalite they probably represent melanosomes after incorporated xenoliths. Microgranular and coarse-grained granitoid enclaves apparently represent stoped autoliths of both quenched and slowly cooled granitic melt in the multiply-intrusive granitoid bodies.